2009
DOI: 10.2215/cjn.02940509
|View full text |Cite
|
Sign up to set email alerts
|

p-Cresyl Sulfate and Indoxyl Sulfate in Hemodialysis Patients

Abstract: Background and objectives: Indoxyl sulfate and p-cresyl sulfate are important representatives of the protein-bound uremic retention solutes. Serum levels of p-cresyl sulfate and indoxyl sulfate are linked to cardiovascular outcomes and chronic kidney disease progression, respectively. They share important features such as the albumin-binding site, low dialytic clearance, and both originate from protein fermentation. Whether serum concentrations are related is, however, not known.Design, setting, participants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
135
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(143 citation statements)
references
References 27 publications
6
135
0
2
Order By: Relevance
“…These findings, coupled with knowledge that the enzymes that produce p-cresol and indole are irregularly present among the myriad types of colon microbes, could account for many features of PCS and IS production (28,29). As observed in prior studies, we found that PCS and IS production rates were poorly correlated in individual participants, which could be explained by differences in the microbial flora of different individuals (30). In addition, the variation in PCS and IS production among individuals was much larger than the variation in urea production, and the correlations between PCS and IS production and protein and fiber intake were weak.…”
Section: Discussionsupporting
confidence: 78%
“…These findings, coupled with knowledge that the enzymes that produce p-cresol and indole are irregularly present among the myriad types of colon microbes, could account for many features of PCS and IS production (28,29). As observed in prior studies, we found that PCS and IS production rates were poorly correlated in individual participants, which could be explained by differences in the microbial flora of different individuals (30). In addition, the variation in PCS and IS production among individuals was much larger than the variation in urea production, and the correlations between PCS and IS production and protein and fiber intake were weak.…”
Section: Discussionsupporting
confidence: 78%
“…7,8 As a consequence, decrease in concentration of intestinally generated uremic retention solutes, like indole, by the intestinal sorbent AST-120 (Kremezin) has been accepted in mostly Asian countries as a strategy to restrain the progression of CKD. In a recent large randomized controlled trial in the United States and Europe, however, this positive effect could not be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Dialysis is usually not powerful to remove protein-bound uremic toxins alone. 7,8 AST-120 (Kremezin), however, in a recent large randomized controlled trial in the United States and Europe, the positive effect of removing indoxyl sulfate could not be confirmed.…”
Section: Introductionmentioning
confidence: 98%
“…More recently, a direct association between indoxyl sulfate and cardiovascular outcomes was observed (13). Intriguingly, whereas p-cresyl sulfate and indoxyl sulfate behave similarly during dialysis and share the same albumin binding site, total serum concentrations in hemodialysis patients are unrelated (14).…”
mentioning
confidence: 99%